Nguni diviners and the south-eastern San: some issues relating to their mutual cultural influence - Jolly, P. (Southern African Humanities, 2021)
This article forms a response to issues raised by Prins (1999) concerning the claimed influence of San related beliefs and rites on those of Nguni diviners, specifically Prins's main diviner informant, Togu Sipani. It is argued that, whatever paradigm one may adopt with respect to the interpretation of oral data, the gross inconsistencies in Sipani's testimony to Prins and myself cannot be explained without concluding that this diviner provided information concerning San influence on his rites and beliefs which he believed Prins would like to hear. The claim by Prins that I failed to provide Sipani with a small fee or present to be directed towards his ancestors, supposedly causing him to mislead me with incorrect information, is dismissed as false. Evidence is also provided to support the thesis, disputed by Prins, that central beliefs and rites associated with diviners would have been transmitted from black farmers to some south-eastern San, both in the recent and in the more distant past, and that the imagery associated with the altered states of diviners, as well as other imagery derived in whole or part from the cultures of black farmers, is likely to be represented in San art.